Upgrade Dribbling Learning Achievement Through Differentiated Learning for Middle School Students - Suwardi (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The study aims to improve basketball dribbling skills through differentiated learning for grade VIII students at a public middle school. This research is classroom action research. We conducted this research in two cycles, each involving planning, action implementation, observation, and reflection. The subjects of the study were 28 grade VIII students of public Middle School 3 Bontomarannu. The study collected data through tests and observations. We conducted the data analysis using qualitative descriptive techniques, specifically percentage techniques. The study's findings revealed that in Cycle I, out of 28 students, the learning achievement for front basketball dribbling in grade VIII at public Middle School 3 Bontomarannu were as follows: 43%, or 12 students, met the completion criteria, while 57%, or 16 students, fell short. In Cycle II, the number of students who met the completion criteria increased to 82%, or 22 students, while only 18%, or 6 students, met the incomplete criteria. The data analysis results above suggest that differentiated learning can enhance the basketball dribbling learning achievement for grade VIII students at public Middle School 3 Bontomarannu.